Bleeding Risk Following Stereotactic Body Radiation Therapy for Localized Prostate Cancer in Men on Baseline Anticoagulant or Antiplatelet Therapy - Pepin, Abigail; Shah, Sarthak; Pernia, Monica; Lei, Siyuan; Ayoob, Marilyn; Danner, Malika; Yung, Thomas; Collins, Brian T.; Suy, Simeng; Aghdam, Nima; Collins, Sean P. (Frontiers in Oncology, 2021)
Purpose: Patients on anticoagulant/antiplatelet medications are at a high risk of bleeding following external beam radiation therapy for localized prostate cancer.1 SBRT may reduce the bleeding risk by decreasing the volume of bladder/rectum receiving high doses. This retrospective study sought to evaluate the rates of hematuria and hematochezia following SBRT in these patients. Methods: Localized prostate cancer patients treated with SBRT from 2007 to 2017 on at least one anticoagulant/antiplatelet at baseline were included. The minimum follow-up was 3 years with a median follow-up of 72 months. Patients who had a rectal spacer placed prior to SBRT were excluded. Radiotherapy was delivered in 5 fractions to a dose of 35 Gy or 36.25 Gy utilizing the CyberKnife system. Hematuria and hematochezia were prospectively assessed before and after treatment using the Expanded Prostate Cancer Index Composite (EPIC-26). Toxicities were scored using the CTCAE v4. Cystoscopy and colonoscopy findings were retrospectively reviewed. Results: Forty-four men with a median age of 72 years with a history of taking at least one anticoagulant and/or antiplatelet medication received SBRT. Warfarin (46%), clopidogrel (34%) and rivaroxaban (9%) were the most common medications. Overall, 18.2% experienced hematuria with a median time of 10.5 months post-SBRT. Altogether, 38.6% experienced hematochezia with a median time of 6 months post-SBRT. > Grade 2 hematuria and hematochezia occurred in 4.6% and 2.5%, respectively. One patient required bladder neck fulguration and one patient underwent rectal cauterization for multiple non-confluent telangiectasia. There were no grade 4 or 5 toxicities. Cystoscopy revealed bladder cancer (40%) and benign prostatic bleeding (40%) as the most common hematuria etiology. Colonoscopy demonstrated hemorrhoids (54.5%) and radiation proctitis (9.1%) as the main causes of hematochezia. There was no significant change from the mean baseline EPIC-26 hematuria and hematochezia scores at any point during follow up. Conclusion: In patients with baseline anticoagulant usage, moderate dose prostate SBRT was well tolerated without rectal spacing. High grade bleeding toxicities were uncommon and resolved with time. Baseline anticoagulation usage should not be considered a contraindication to prostate SBRT.